High-Intensity Implantation of Metal Ions in Conditions of Minimizing Ion Sputtering of the Material Surface; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Sivin D. O. Denis Olegovich; Ryabchikov A. I. Aleksandr Ilyich; Ananin P. S. Petr Semenovich; Stepanov I. B. Igor Borisovich; Modebadze G. S. Georgy Slavovich; Koval T. V. Tamara Vasilievna (Ion Beam Processing of Materials. Poster Session, 2019)
Заглавие с экрана